The fortunes of Indigo Skye - Caletti, Deb. (New York : Simon & Schuster Books for Young Readers, 2008)
Eighteen-year-old Indigo is looking forward to becoming a full-time waitress after high school graduation, but her life is turned upside down by a large check given to her by a customer who appreciates that she cares enough to scold him about smoking.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Diners (Restaurants) -- Juvenile fiction; Families -- Washington (State) -- Juvenile fiction; Single-parent families -- Juvenile fiction; Waiters -- Juvenile fiction; Wealth -- Juvenile fiction; Diners (Restaurants) -- Fiction; Family life -- Washington (State) -- Fiction; Single-parent families -- Fiction; Waiters and waitresses -- Fiction; Wealth -- Fiction; Diners (Restaurants) -- Fiction; Family life -- Washington (State) -- Fiction; Single-parent families -- Fiction; Waiters and waitresses -- Fiction; Wealth -- Fiction; Washington (State) -- Juvenile fiction; Washington (State) -- Fiction; Washington (State) -- Fiction